Pengaruh sikap terhadap kesejahteraan hidup petani padi di kawasan MADA dan luar MADA di negeri Perlis dengan pendekatan analisis kehidupan lestari - Azizah, Md Yusof (2018)
This study was conducted to investigate the level of farmers’ well-being in MADA and outside the MADA rice fields in Perlis. Low levels of well-being amongst these farmers have been associated with attitude problems. It is generally known that the government has provided assistance to farmers to improve their livelihood assets. Hence, it is claimed that attitude and livelihood assets can affect farmers’ well-being. This study examined the truth regarding the importance of attitude in influencing the well-being of farmers. The general objective of the study was to analyze the role of attitude, livelihood assets, threats and institutions on farmers’ well-being in MADA and outside the MADA areas. The Sustainable Livelihood Analysis Framework (AKL) was used in this study. A total of 347 farmers in MADA and 330 farmers from outside MADA were used as respondents. The Structural Equation Modeling (SEM) was used to analyze the data and in developing a model of farmers’ well-being in both areas. The study found that the livelihood assets and the well-being of farmers in the MADA area were better than those outside the MADA area. Threats, livelihood assets and institutions have positively influenced the well-being of farmers in the MADA area. However, institutions were not significant outside the MADA area. All of these variables indirectly affect the farmers’ well-being through the attitude variables. Attitude is a full mediator in connecting threats, livelihood assets and institutions with farmers’ well-being. This means, without the attitude variables, these three variables will not affect the farmers’ well-being. Therefore, proper emphasis should be placed on changing the attitudes of the farmers before implementing any programs to improve well-being. This study proves that attitude is an important variable in improving farmers’ well-being. In terms of policy implications, the government needs to focus on creating a positive attitude amongst farmers so that all efforts undertaken by the government in improving the well-being of the farmers will produce the expected results.